New Insights Into CRASP-Mediated Complement Evasion in the Lyme Disease Enzootic Cycle - Lin, Yi-Pin; Frye, Amber M.; Nowak, Tristan A.; Kraiczy, Peter (Frontiers in Cellular and Infection Microbiology, 2020)
Lyme disease (LD), which is caused by genospecies of the Borrelia burgdorferi sensu lato complex, is the most common vector-borne disease in the Northern hemisphere. Spirochetes are transmitted by Ixodes ticks and maintained in diverse vertebrate animal hosts. Following tick bite, spirochetes initially establish a localized infection in the skin. However, they may also disseminate hematogenously to several distal sites, including heart, joints, or the CNS. Because they need to survive in diverse microenvironments, from tick vector to mammalian hosts, spirochetes have developed multiple strategies to combat the numerous host defense mechanisms. One of these strategies includes the production of a number of complement-regulator acquiring surface proteins (CRASPs) which encompass CspA, CspZ, and OspE paralogs to blunt the complement pathway. These proteins are capable of preventing complement activation on the spirochete surface by binding to complement regulator Factor H. The genes encoding these CRASPs differ in their expression patterns during the tick-to-host infection cycle, implying that these proteins may exhibit different functions during infection. This review summarizes the recent published reports which investigated the roles that each of these molecules plays in conferring tick-borne transmission and dissemination in vertebrate hosts. These findings offer novel mechanistic insights into LD pathobiology and may facilitate the identification of new targets for preventive strategies against Lyme borreliosis.